Constructing Catalan Identity Memory, Imagination, and the Medieval - Vargas, Michael A. (Springer International Publishing, 2018)
This is a book about how Catalans use their past, real and imagined, in the construction of their present and future. Michael A. Vargas inventories the significant people, signal events, and familiar icons that constitute the Catalan collective memory, from Wilfred the Hairy and Sant Jordi to the mountain monastery of Montserrat, red peasant caps, and human towers in town squares. He then considers how that inventory is employed to posit a brilliant political heritage at the forefront of modern European democracy-and for some, to build a powerful independence movement. As the future of Catalonia remains fraught, this book offers a lively and engaging exploration of how we draw upon history to confront contemporary challenges.